Technology development and evolution trend of all-optical switching networks - Min ZHOU; Jian ZHANG; Yin WANG (Dianxin kexue)
In the 5G era,growth of network traffic is driven by the development of emerging services,especially the burst of east-west traffic.The network evolved from a multi-layered planar architecture to a three-dimensional architecture,thereby promoting the development and application of all-optical switching technology.The development and technology evolutions of optical switching architecture were introduced,the key enabling technologies and applications of all-optical switching equipment were described,and the future trends of all-optical switching technology were discussed.